Developing Students’ Tolerance in Religious Life through Multicultural Education in Setia Budi Senior High School, Sungailiat Bangka - Soleha, Soleha; Maryam, Maryam (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
One of the values of the Indonesian nation's character that must be developed in our education process is tolerance. This research is important in order to see the implementation of the inculcation of tolerance in religion through multicultural education. This study tries to answer questions about the implementation of the inculcation of students' tolerance in religious life through multicultural education in Setia Budi Sungailiat High School, Bangka Regency. The findings in this study are the inculcation of students' tolerance in religious life through multicultural education conducted at Setia Budi High School, is the application of one of the policies set by the school to create religious tolerance in the school environment. This inculcation of religious tolerance will go well, if all school members understand, respect each other, and value the differences arranged in a multicultural education concept.